2019
DOI: 10.3390/ani9080544
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, Attitudes and Self-Efficacy of Australian Veterinary Students Regarding One Health and Zoonosis Management

Abstract: This study aimed to explore the beliefs and attitudes of a group of senior veterinary students regarding One Health and to evaluate their levels of confidence in advising the general public on preventative health issues at the human–animal interface. An online survey was communicated to senior veterinary students who were in their last two years of study. The questionnaire covered beliefs and attitudes, issues concerning the animal–human interface and participants’ confidence in diagnosing zoonoses. In total, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…There is tentative evidence that this would be welcomed by students, especially vet students. In a UK survey, 69% of vet students, and 42% of pharmacy students reported wanting more education on the links between human, animal, and environmental health [ 56 ], and in an Australian survey, vet students had positive attitudes towards One Health approaches in both training and practice [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is tentative evidence that this would be welcomed by students, especially vet students. In a UK survey, 69% of vet students, and 42% of pharmacy students reported wanting more education on the links between human, animal, and environmental health [ 56 ], and in an Australian survey, vet students had positive attitudes towards One Health approaches in both training and practice [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our findings more than 95% of students reported having good understanding of AMS. In Australia, one survey [39] has shown that more than 80% of veterinary students, while another study [74] has shown that more than 60% of them perceived that statement. Contrary, in Nigeria a very low percentage of veterinary students (13.1%) [75] and veterinarians (17.1%) [76] have heard about AMS, as well as only about 24% of pharmacy students in Saudi Arabia [77].…”
Section: Plos Onementioning
confidence: 99%
“…Veterinarians are trained to help prevent the transmission of zoonotic diseases by recognizing and treating diseases in companion and food animals; these professionals play an essential role in promoting public health by educating clients about disease transmission from animals to humans [ 7 ]. Veterinary knowledge of zoonotic disease prevention and suspected case management is crucial—veterinarians are at the frontline of defense against zoonoses’ entry into the human population [ 8 ]. In the United Arab Emirates (UAE), a five-year veterinary medicine program was launched in 2013, and the first-ever batch of Emirati veterinary doctors was graduated in 2018 from the United Arab Emirates University (UAEU) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%